The Gospel According to The Simpsons : the spiritual life of the world's most animated family - Pinski, Mark I. (Westminster John Know Press, 2001)
Is there anything holy in Springfield, the home to irascible Bart Simpson and his naive dad Homer, their enthusiastic evangelical neighbor Ned Flanders, the sourpuss minister Rev. Lovejoy, and the dozens of other unique characters who inhabit the phenomenally popular TV show? In this revision of the 2001 bestseller, author Mark Pinsky says yes!In this entertaining and enlightening book, Pinsky shows how The Simpsons engages issues of religion and morality in a thoughtful, provocative, and genuinely respectful way. With three new chapters and updates to reflect the 2001-2006 seasons, Pinsky has given a thorough facelift to the book that Publishers Weekly called "thoughtful and genuinely entertaining."The new material includes chapters on Buddhism and gay marriage and an extensive afterword that explores how religion is treated on the animated shows that have followed in the footsteps of The Simpsons: South Park, Family Guy, Futurama, American Dad, and King of the Hill.